Manajemen Pembelajaran Santri Taman Pendidikan Al-Qu’ran (TPA) Darus Sakinah Sangatta Utara - Ramdanil Mubarok (Al-Rabwah, 2020)
To produce competent graduates in the field of al-Qur'an, learning management is needed. How is the learning management of students in the al-Qur'an educational park in the community of Darus Sakinah? The aim is to find out the management of the students in the al-Qur'an educational park at the Darus Sakinah mosque. This research is a descriptive field research. The subjects of this study were the head of the al-Qur'an educational park, asatidz and asatidzah, the management of the Darus Sakinah mosque, by conducting observations, interviews and documentation. The data checking was done by triangulation of sources, triangulation of techniques and triangulation of time. The conclusion is that the learning management of students in the al-Qur'an education park Darus Sakinah has been going well. By taking steps in accordance with the principles of management implementation. Namely, there is planning before learning begins, there is organization in terms of scheduling, class grouping, to the flexibility of the learning schedule, then there is implementation, namely the implementation of learning by referring to previous planning, as well as monitoring and evaluation to identify, measure, find solutions to the shortcomings there is.